2004
DOI: 10.1590/s0100-204x2004000200014
|View full text |Cite
|
Sign up to set email alerts
|

Fertility life table of Trichogramma pretiosum and Trichogramma acacioi on eggs of Anagasta kuehniella at different temperatures

Abstract: -Species of the Trichogramma genus are among the most important ones for biological control. The objective of this research was to evaluate parasitism potential of two species of Trichogramma on eggs of Anagasta kuheniella through life fertility table, at temperatures between 15 o C and 35 o C. These species were collected in the State of Espírito Santo parasitising eggs of the avocado defoliator Nipteria panacea. Trichogramma pretiosum and T. acacioi showed adequate reproductive potential between 15 o C and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 8 publications
5
13
0
7
Order By: Relevance
“…2). Longer longevity of T. pretiosum (22 days) and T. acacioi (8 days) at temperature similar to their thermal inferior limits confirmed the reports of these species being collected at altitudes near 1.000 m. However, T. pretiosum presented an inverse relationship between longevity and temperature increase which indicated that the effect of this parameter varied with Trichogramma species (Maceda et al 2003;Pratissoli et al, 2004b;Pratissoli et al, 2005b). Parasitism potential of T. pretiosum was also found to be directly related to the lineage of this parasitoid and to the host and weather conditions (Inoue and Parra, 1998;Faria et al, 2000;Pratissoli and Parra, 2000;2001;Pratissoli et al, 2004b Means followed by the same letter, in each column, do not differ between themselves by the test of Tukey at 5% probability level.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…2). Longer longevity of T. pretiosum (22 days) and T. acacioi (8 days) at temperature similar to their thermal inferior limits confirmed the reports of these species being collected at altitudes near 1.000 m. However, T. pretiosum presented an inverse relationship between longevity and temperature increase which indicated that the effect of this parameter varied with Trichogramma species (Maceda et al 2003;Pratissoli et al, 2004b;Pratissoli et al, 2005b). Parasitism potential of T. pretiosum was also found to be directly related to the lineage of this parasitoid and to the host and weather conditions (Inoue and Parra, 1998;Faria et al, 2000;Pratissoli and Parra, 2000;2001;Pratissoli et al, 2004b Means followed by the same letter, in each column, do not differ between themselves by the test of Tukey at 5% probability level.…”
Section: Resultssupporting
confidence: 54%
“…Daily parasitism and parasitism period of Trichogramma may vary among the species, lineage, host, temperature and climatic conditions (Pratissoli et al, 2004a;Pratissoli et al, 2004c;Oliveira et al, 2005). Many species of this genus present maximum fecundity around 25°C with decreasing values at extreme temperatures (Pratissoli et al, 2004b;Pratissoli et al, 2005a). The objective of this study was to evaluate the parasitism capacity of Trichogramma pretiosum Riley and T. acacioi Brun; Moraes; Soares (Hymenoptera: Trichogrammatidae) in the eggs of the alternative host Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) in order to use them in biological control programs of N. panacea.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of parasitism can be affected by various factors, including the species of parasitoid host, number of generation of the parasitoid maintained in the laboratory, and alternative hosts used for rearing (Pratissoli & Oliveira 1999), as well as biological characteristics of the host itself (Pratissoli et al 2004a). However, the present study has demonstrated that the consumption of pollen from Bt maize had little effect on the biological characteristics of the T. pretiosum parasitoid, over 4 generations.…”
Section: Discussionmentioning
confidence: 99%
“…Em espécies de Trichogramma, as fêmeas, quando jovens, apresentam maior taxa de oviposição, a qual se reduz gradativamente com a idade (Pratissoli et al, 2004;Zago et al, 2006). Tais observações também foram registradas por Pratissoli et al (2007), que estudaram as diferentes idades de fêmeas de T. pretiosum sobre ovos de P. xylostella e observaram redução na capacidade de parasitismo dessa espécie.…”
Section: Methodsunclassified